Validation of aerosol measurements from the improved stratospheric and mesospheric sounder - Lambert, A; Grainger, R; Remedios, J; Reburn, W; Rodgers, C; Taylor, F; Roche, A; Kumer, J; Massie, S; Deshler, T (Blackwell Publishing Ltd, 1996)
Atmospheric temperature measurements from the improved stratospheric and mesospheric sounder (ISAMS) are evaluated. Flown on the Upper Atmosphere Research Satellite (UARS), ISAMS obtained 180 days of science data between September 26, 1991 and July 29, 1992. Typically, over 2600 temperature profiles/day were retrieved, spaced every 200 km along the limb-viewing track and nominally extending from 100 to 0.01 mbar (15-80 km). The latitude coverage ranged from 80°S to 80°N, depending on the particular ISAMS/UARS viewing geometry on any day. UARS is in a near-Sun-synchronous orbit, so that while the 15 orbits/d are spaced approximately every 24° longitude around the equator, the sampled local solar time actually changes by 20 min/d. The ISAMS temperature retrieval process is outlined and the various products are described. A detailed error budget for the retrieval is presented and comparisons are made with temperature measurements from other sources. Finally, a table is provided summarizing the best estimates of ISAMS temperature bias and precision. The results suggest a general cold bias of around 1 K in the stratospheric temperatures, with a superimposed 2-3 K warm bias associated with the densest part of the Pinatubo aerosol cloud. The precision of individual profiles is ±2 K throughout the stratosphere but falls off in the mesosphere to about ±10 K at 80 km. The error bars produced by the retrieval appear to be reasonable (although slightly pessimistic) estimates of the precision. Copyright 1996 by the American Geophysical Union.